A New Method for Measuring Bell-Shaped Chest Induced by Impaired Ribcage Muscles in Spinal Muscular Atrophy Children - LoMauro, Antonella; Banfi, Paolo; Mastella, Chiara; Alberti, Katia; Baranello, Giovanni; Aliverti, Andrea (Frontiers in Neurology, 2018)
The involvement of the respiratory muscular pump makes SMA children prone to frequent hospitalization and morbidity, particularly in type 1. Progressive weakness affects ribcage muscles resulting in bell-shaped chest that was never quantified. The aims of the present work were: 1)to quantify the presence of bell-shaped chest in SMA infants and children and to correlate it with the action of ribcage muscles, assessed by the contribution of pulmonary ribcage to tidal volume (ΔVRCp); 2)to verify if and how the structure of the ribcage and ΔVRCp change after one-year in SMA type 2. 91 SMA children were studied in supine position during awake spontaneous breathing: 32 with type 1 (SMA1, median age: 0.8 years), 51 with type 2 (SMA2, 3.7 years), 8 with type 3 (SMA3, 5.4 years) and 20 healthy children (HC, 5.2 years). 14 SMA2 showed negative ΔVRCp (SMA2px), index of paradoxical inspiratory inward motion. The bell-shaped chest index was defined as the ratio between the distance of the two anterior axillary lines at sternal angle and the distance between the right and left 10th costal cartilage. If this index was << 1, it indicated bell shape, if ~1 it indicated rectangular shape, while if >> 1 an inverted triangle shape was identified. While the bell-shaped index was similar between HC (0.92) and SMA3 (0.91), it was significantly (p<0.05) reduced in SMA2 (0.81), SMA2px (0.74) and SMA1 (0.73), being similar between the last two. There was a good correlation (Spearman's rank correlation coefficient, ρ=0.635, p<0.001) between ribcage geometry and ΔVRCp. After one year, ΔVRCp reduced while bell-shaped chest index did not change being significantly lower than HC. The shape of the ribcage was quantified and correlated with the action of ribcage muscles in SMA children. The impaired ribcage muscles function alters the ribcage structure. HC and SMA3 show an almost rectangular ribcage shape, whereas SMA2, SMA2px and SMA1 are characterized by bell-shaped chest. In SMA, therefore, a vicious cycle starts since infancy: the disease progressively affects ribcage muscles resulting in reduced expansion of lung and ribcage that ultimately alters ribcage shape. This puts the respiratory muscles at mechanical disadvantage.